How Far Has the Progressed Since Its Transformation Into an English Language Journal? - Sun Huh (International Neurourology Journal, 2014)
PurposeThe publisher of the International Neurourology Journal changed the text to English in 2010 to promote the journal as an international publication. Four years later, what has happened to this journal? This paper will use citation indicators to describe the degree of internationalization.MethodsCitation indicators such as impact factors, total citations from Web of Science, Science Journal Rankings (SJR), cites per documents (2 years), and Hirsch indexes (h-indexes) from Web of Science, digital object identifier (DOI)/CrossRef, ScimagoJR, or Scopus were calculated. In addition, the native countries of the authors and researchers citing the journal in Web of Science were analyzed.ResultsImpact factors in 2012 and 2013 were 0.645 and 0.857, respectively. Total citations in 2011, 2012, and 2013 from Web of Science were 15, 51, and 99, respectively, and the SJRs in 2011 and 2012 were 0.220 and 0.390, respectively. The h-indexes from DOI/CrossRef, Scopus, and Web of Science were 7, 8, and 6, respectively. Out of 153 unsolicited published papers, 27 (17.6%) were from outside of Korea. The researchers citing the journal in Web of Science and Scopus were primarily from the United States, Korea, China, the United Kingdom, and France. Funding agencies supported 39 of 101 original articles (38.6%).ConclusionsAfter changing the text to the English language, the citation indicators show that the International Neurourology Journal has been elevated to an international journal. Although the nationality of authors varies from year to year, the increase in the number of manuscripts from international authors is obvious.